(untitled) (Communications in Mathematical Research, 2021)
In this paper, we give transcendence bases of the rational invariants fields of the generalized classical groups and their subgroups B, N and T , and we also compute the orders of them. Furthermore, we give explicit generators for the rational invariants fields of the Borel subgroup and the Neron-Severi subgroup of the general linear group.